County-level social factors and schizophrenia: A multilevel study of 1.9 million Chinese adults. (January 2019) - Luo, Yanan; Guo, Chao; Zhang, Lei; Pang, Lihua; Zhao, Xin; Zheng, Xiaoying
Highlights: Investigation about the association between county-level social factors and schizophrenia. County-level social factors were associated with schizophrenia. Strategies to improve access to health services for individuals in high urbanization rates areas are needed. Public policies that seek to promote gender equality in areas with high SEC and divorce rates will improve females' mental health. Abstract: There is little evidence on the association between area-level social factors and schizophrenia in China. This study aimed to investigate the relationship between county-level social factors and schizophrenia in Chinese adults aged 18 years old and above. We obtained data from the Second China National Sample Survey on Disability, and selected 1, 909, 205 adults for analysis. Schizophrenia was ascertained according to the International Statistical Classification of Diseases, Tenth Revision. Multilevel logistic regressions showed that areas with higher urbanization rate was associated with increased risk of schizophrenia (areas with moderate urbanization rate: OR = 1.28, 95% CI: 1.15, 1.44; areas with high urbanization rate: OR = 1.48, 95% CI: 1.26, 1.75). Stratified analyses found that, in female adults, urbanization rates, divorce rates and socioeconomic conditions were positively associated with increased risks for schizophrenia. However, in male adults, low socioeconomic conditions was related to decreased risk of schizophrenia, and there was no significant association between rates of divorce and risks for schizophrenia. In conclusion, county-level social factors, in the form of urbanization rate, divorce rate, and socioeconomic conditions, were associated with the risk of schizophrenia in Chinese adults. Gender differences were found in these associations.